2013
DOI: 10.1590/s1806-83242013000600012
|View full text |Cite|
|
Sign up to set email alerts
|

The influence of desensitizing dentifrices on pain induced by in-office bleaching

Abstract: The purpose of this study was to evaluate whether the use of desensitizing dentifrices used 15 days prior to and after in-office tooth bleaching could eliminate or reduce tooth sensitivity. After institutional review board approval and informed consent, 45 subjects were selected and divided into 3 groups according to the dentifrice selected: Colgate Total (CT), Colgate Sensitive Pro-Relief (CS) or Sensodyne ProNamel (SP). The subjects used toothpaste and a toothbrush provided to them for 15 days prior to bleac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 27 publications
3
22
0
9
Order By: Relevance
“…The reason for this finding may be attributed to the fast that the main mechanism of action of this dentifrice involves the obliteration of exposed root dentin tubules which is not applicable to the cohort studied. This is in accordance with the research of Thiesen et al (1) Group 3 containing Novamin or CSSP represents a method of tubule occlusion consisting of oxides of calcium, sodium, phosphorus ions and help in the formation of hydroxycarbonate apatite (HCA), which is similar in composition to minerals of teeth and bone. (21) This was found to be significantly effective in reducing post-bleaching sensitivity on the first day of both sessions using the subjective scale.…”
Section: Mechanism Of Action Of the Bleaching Agent (Hydrogen Peroxide)supporting
confidence: 89%
See 2 more Smart Citations
“…The reason for this finding may be attributed to the fast that the main mechanism of action of this dentifrice involves the obliteration of exposed root dentin tubules which is not applicable to the cohort studied. This is in accordance with the research of Thiesen et al (1) Group 3 containing Novamin or CSSP represents a method of tubule occlusion consisting of oxides of calcium, sodium, phosphorus ions and help in the formation of hydroxycarbonate apatite (HCA), which is similar in composition to minerals of teeth and bone. (21) This was found to be significantly effective in reducing post-bleaching sensitivity on the first day of both sessions using the subjective scale.…”
Section: Mechanism Of Action Of the Bleaching Agent (Hydrogen Peroxide)supporting
confidence: 89%
“…The main intrinsic causes of discoloration are aging and necrosis of pulp, while those of extrinsic discoloration are pigments from common beverages and tobacco. (1)(2)(3)(4) One of the commonest measures adopted to manage discoloured teeth is In-office vital tooth bleaching, because of its conservative approach and high success rate. (1,2) Hydrogen peroxide, at varying concentrations, is usually the chief ingredient in bleaching materials used for this purpose.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Most clinical studies have shown that both approaches effectively reduce TS. 4,[8][9][10][11] However, because neurogenic inflammation may play a role in TS resulting from tooth bleaching, 2,10 we hypothesize that desensitizing products should prevent the bleaching product from reaching the pulp by obliterating the dentin tubules more quickly and consequently preventing the inflammation rather than by simply inhibiting the painful neural stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…Another study found that a 5% potassium nitrate and 2% sodium fluoride gel used before in-office bleaching decreased the incidence of sensitivity (6). Additionally, the use of potassium nitrate toothpaste before whitening has been shown to reduce sensitivity during and after tooth-whitening procedures (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%